Comparative study of electrically and inductively actuated shape memory alloy niti wire using tensile testing - Karunakaran, Sivasanghari; Abang Abdul Majid, Dayang Laila; Imran, Husam Yahya (UTM Publisher, 2024)
Shape memory alloy (SMA) actuators have the capability to actuate high forces while being compact, making them a potential replacement for complex electromechanical systems especially in aerospace applications. Common heating technique of SMA actuator is electrical heating. However, the actuation capability of SMA is dependent on the heat transfer mechanism of SMA as it is very sensitive to temperature and stress, thus lead to the difficulty in controlling mechanism. Owing to the complex controllability of heating techniques, the induction heating technique for SMA wire was undertaken in this investigation and proposed to be promising technique for SMA. A comparison between electrical heating and induction heating were performed using tensile testing. The tensile loading was performed using Instron 3366 Universal Testing Machine (UTS) with a 5 kN load cell and strain rate of 0.04 mm/min. A series of experiment at three different activation temperatures of 60°C,70°C and 80°C were performed for both the electrical and induction heating technique. The electrical actuation was done through power supply, whereas the inductive actuation was done through a specially developed heat control chamber comprises electromagnetic coil. The stress-strain curve for loading path was developed for both techniques and were compared. The results showed that the loading profile for inductively actuated wire was similar to the loading pattern of SMA superelasticity performance compared to electrical actuated wire which was nonlinear and serrated. In conclusion, induction heating technique is seemed to be a promising method to actuate SMA precisely.